2014
DOI: 10.11591/ijece.v4i5.6447
|View full text |Cite
|
Sign up to set email alerts
|

Voice-Based Door Access Control System Using the Mel Frequency Cepstrum Coefficients and Gaussian Mixture Model

Abstract: Access to an area or environment can be controlled by conventional and electronic keys, identity cards, personal identification numbers (PINs) pads and smartcards. Due to certain limitations of existing door access schemes deployed for security in buildings, this paper presents speaker recognition for building security as a better means of admission into important places. This is proposed due mainly to the fact that speech cannot be stolen, copied, forgotten, lost or guessed with accuracy. This paper, therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Some event-based method using algorithm for real-time event detection such as change point detection [6], Generalized Likelihood Ratio (GLR) [7], the chi-square goodness-of-fit test (X2 GOF) [8], the Cumulative SUM (CUSUM) filtering [9], and cepstrum analysis [10]- [13]. Change point detection to detect abrupt changes in time series data and to identify the specific time instance when the change occurs.…”
Section: Related Workmentioning
confidence: 99%
“…Some event-based method using algorithm for real-time event detection such as change point detection [6], Generalized Likelihood Ratio (GLR) [7], the chi-square goodness-of-fit test (X2 GOF) [8], the Cumulative SUM (CUSUM) filtering [9], and cepstrum analysis [10]- [13]. Change point detection to detect abrupt changes in time series data and to identify the specific time instance when the change occurs.…”
Section: Related Workmentioning
confidence: 99%
“…The research on Automatic Speech Recognition (ASR) is still the most interest topic for its very important role in daily life such as in the number of works that have been conducted on SR (Speech Recognition) such as Smart Home [1][2][3][4], Artificial Intelligence such as human emotional classification based on speech recognition [5][6][7][8][9] and robotic application [10], in the field of Student Learning [11][12][13], in medical sector, SR is used to detect the stress level of a person [14]. Therefore, the optimization process in SR is still in the progress for obtaining the better accuracy such as with speech enhancement [15][16][17] or noise reduction [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of identifying spoken words can be displayed in written form or can be read by technological devices. Recognition of words through voice signals has been carried out by many previous studies, one of them is Makhraj recognition for Al-Quran recitation [1], voice-based door access control system [2], pronunciation of the alphabet in English [3], language recognition Bengali automatically [4], play songs automatically [5]. While other study identified speaker [6], recognized of a person through footstep sound [7], identified Qori reciter in Arabic [8], identified speakers with whispered speech audio flow [9].…”
Section: Introductionmentioning
confidence: 99%